EXPERIENCE OF TREATMENT WITH INHIBITOR OF T-LYMPHOCYTES CO-STIMULATION ABATACEPT IN PATIENT WITH POLYARTICULAR TYPE OF JUVENILE RHEUMATOID ARTHRITIS - T.M. Bzarova; E.I. Alexeeva; S.I. Valieva; A.M. Chomakhidze; K.B. Isaeva; A.O. Lisitsyn; R.V. Denisova (Вопросы современной педиатрии, 2010)
The article presents a case report of recurrent clinical course of polyarticular type of juvenile rheumatoid arthritis, which is characterized with rapid development of disability, low quality of life, high index of functional insufficiency, torpid flow. The disease developed with intolerance to metotrexate and presence of contra-indications to blockers of tumor necrotizing factor _. Authors describe successful treatment with inhibitor of T-lymphocytes co-stimulation abatacept. The dose of drug was 10 mg/kg of body weight during 24 weeks. In two weeks after the beginning of treatment pain and exudative lesions in joints were lessened, joint range of motions significantly increased. The quality of life of patient and her family increased in 4 weeks of treatment with abatacept. The drug induced clinical and laboratory remission in 24 weeks.Key words: children, juvenile rheumatoid arthritis, abatacept, treatment.(Voprosy sovremennoi pediatrii — Current Pediatrics. – 2010;9(4):147-154)